Further studies on the effects of supplementing groundnut hulls with dried poultry excreta or cotton seed cake on performance of Sudan Desert sheep - El Hag, M.G.; El Hag, G.A. (1981)
The study presents results of experiment undertaken to evaluate the nutritive value of poultry litter as part of a sheep ration replacing cotton-seed cake, utilizing measurements of chemical composition, in vitro as well as in vivo digestibility, voluntary intake, animal performance and carcass characteristics of meat from animals given the diet containing poultry excreta.